2004
DOI: 10.1177/147323000403200101
|View full text |Cite
|
Sign up to set email alerts
|

Acute Streptococcal Tonsillopharyngitis: A Review of Clinical Efficacy and Bacteriological Eradication

Abstract: comparing clinical outcome and bacteriological eradication rates for patients with acute streptococcal tonsillopharyngitis treated with penicillin or other antimicrobial agents. Studies were identified using MEDLINE, and clinical outcome and bacteriological eradication at end of treatment and 2 weeks after end of treatment were ascertained. Any longerterm follow-up was also noted, along with treatment-related adverse events and compliance. Clinical efficacy rates between penicillin and comparator antibiotics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
2
5
0
1
Order By: Relevance
“…Bacteriological eradication was less in azithromycin 10 mg/kg/day groups (38-58%) compared to penicillins (81-84%) whereas azithromycin 20 mg/kg/day therapy achieved bacteriological eradication in 95% cases. Authors suggested that a higher dose of azithromycin was more appropriate for management of acute Streptococcal tonsillopharyngitis [21]. Bacteriological eradication is more important from point of view of preventing progression of pharyngitis to acute rheumatic fever.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriological eradication was less in azithromycin 10 mg/kg/day groups (38-58%) compared to penicillins (81-84%) whereas azithromycin 20 mg/kg/day therapy achieved bacteriological eradication in 95% cases. Authors suggested that a higher dose of azithromycin was more appropriate for management of acute Streptococcal tonsillopharyngitis [21]. Bacteriological eradication is more important from point of view of preventing progression of pharyngitis to acute rheumatic fever.…”
Section: Discussionmentioning
confidence: 99%
“…11 The use of BPG injection was considered unethical, dangerous, less efficacious, and even fatal in certain cases; therefore, studies with a direct comparison with azithromycin were not done, but the review of the literature showed azithromycin to be the best drug for GABHS. 12 ARMOR: Azithromycin must be given in a dose of 500 mg one tablet daily for 5 days, followed by one tablet once a week for 1 year for primary prevention, treatment and secondary prophylaxis of RF/RHD, respectively. 13…”
Section: The Miracle Solution Is As Followsmentioning
confidence: 99%
“…This failure probably stems from the fact that about 20% of children with GABHS is infected with bacteria which contain M protein, a virulence factor located on the surface of the bacterial wall that confers resistance to commonly used antibiotics [12]. Newer beta-lactamase-resistant antibiotics did not prevent this treatment failure [13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…Review of the literature from 1945 to 1999, which includes 10,484 cases of GABHS sore throat, found that antibiotic treatment reduced the occurrence of acute otitis media, a common complication of this disease, by a mere 25%, compared to the placebo group and sinusitis by only 50% [13]. Rheumatic fever, a nonsuppurative complication, was reduced by less than 33%, compared to placebo [8, 10, 11, 15].…”
Section: Introductionmentioning
confidence: 99%